ANALISIS PEMASARAN GULA AREN DI KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Novia fitri yanti; Suharno Suharno; Harianto Harianto (Politeknik Negeri Lampung, 2018)
Palm sugar is one of the important commodities that are able to sustain the economy of rural community. The community of central palm sugar is usually constrained by market information that affects the welfare of sugar palm producers. The purposes of this research are to observe marketing channels and marketing performance efficiency and to analyze factors influencing producers to choose marketing channel of palm sugar in Bengkulu Province. The result of this research shows there are 5 marketing channels of palm sugar in Bengkulu Province. Measurement of marketing performance efficiency by using margin analysis indicator, farmer's share and r/c ratio, found that efficient channel model with the indicator is channel 4 (Producers-Big Collector in the village-Consumer Outside of the province) and channel 5 (Producers - Big Collector in the village - Retailer local - Local consumers). Factors influencing craftsmen choosing marketing channels were analyzed by using binary logistic regression and it was found that factor of production quantity, sugar price and existence of debt bondage significantly influence producers in choosing marketing channel.Keywords: palm sugar, marketing efficiency, marketing chooice, binary logistic